Impact of late pregnancy haemoglobin A1c at 29–30 weeks' gestation on adverse pregnancy outcomes among women with pre-existing diabetes: a retrospective analysis. (19th May 2018) - Yong, Soon Leong; Ng, Beng Kwang; Mohd Yassin, Muhammad Abdul Jamil; Syed Zakaria, Syed Zulkifli; Mohamed Ismail, Nor Azlin
Abstract: This study was to assess the relationship between late pregnancy haemoglobin A1C (HbA1C ) at 29–30 weeks of gestation and adverse pregnancy outcomes (APOs) in 272 pregnant women with pre-existing diabetes. HbA1C ≥6.1% was associated with significantly increased risk of preterm delivery, Caesarean section, large for gestational age (LGA), neonatal respiratory distress, neonatal hypoglycaemia, and composite adverse neonatal outcome ( p < .05). The risk of pre-eclampsia increased significantly at the lower HbA1C cut-off of > 5.6% ( p = .039). Reduction of HbA1C cut-off from 6.1% to 5.6% improved the sensitivity but reduced the specificity for prediction of APOs. Overall, the receiver operating characteristic (ROC) curves demonstrated the moderate predictive value of late pregnancy HbA1C for APOs. In conclusion, elevated late pregnancy HbA1C levels at 29–30 gestational weeks had a negative impact on APOs in pregnant women with pre-existing diabetes. However, HbA1C cut-off levels of neither ≥6.1% nor >5.6% were ideal for predicting APOs. Impact statement: What is already known on this subject: Poorly controlled diabetes is associated with adverse pregnancy outcomes (APOs). Periconceptual haemoglobin A1C (HbA1C ) correlates well with the risk of foetal anomaly but is not predictive of APOs at time of delivery. New evidence suggested that late pregnancy HbA1C is predictive of APOs but the definitions of a late pregnancy gestational week and target HbA1C cutpoint remain in doubt. What the results of this study add: This study investigated the relationship between late pregnancy HbA1C levels at 29–30 weeks of gestation and the APOs among pregnant women with pre-existing diabetes. Late pregnancy HbA1C ≥ 6.1% correlated with the risk of APOs but the increased risk of pre-eclampsia only became significant at the lower cut-off of >5.6%. Reducing HbA1C cut-off from 6.1% to 5.6% improved the sensitivity but reduced the specificity for prediction of APOs. Overall, late pregnancy HbA1C had a moderate predictive value for APOs. What the implications are of these findings for clinical practice and/or further research: HbA1C cut-off levels of neither ≥6.1% nor >5.6% were ideal in predicting APOs among pregnant women with pre-existing diabetes. As HbA1C levels tend to drop in pregnancy, caution should be taken when interpreting HbA1C in pregnancy. More multi-centred studies are required to explore the respective glycaemic target for each APO and to determine the ideal timing for late pregnancy HbA1C measurement.